ANALISIS IMPLEMENTASI KURIKULUM MERDEKA SERTA RELEVANSINYA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Yulyana, Della; Ariza, Amelia; Indris, Al Ghufron; Ananda, Rizki; Nasrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to identify and obtain information about the implementation of an independent curriculum elementary school levels. The method used in this research is descriptive qualitative method, which describes the subject about the situation and data obtained during observations and question so that it becomes useful information and is easily understood by readers. This study explain and provides an overview of the implementation of the independent curriculum in elementary levels. The results of this study indicate that the implementation of the curriculum in elementary levels is in the pilot phase and is ongoing, by providing several options so that schools have something in accordance with the conditions of their respective schools. The key to the success of implementing the curriculum in schools is competent human resources, in this case teachers. Teachers must have the will to change their mindset so that they can make changes and an independent curriculum can be applied. In addition, there are also facilities and infrastructure to support the implementation of this curriculum to be carried out optimally.   Keywords: curriculum, independent, implementation, school